The Role of Religious Faith on Female Muslim Attitude and Behavior of Charity Intention (Ekonomi Syariah IAIN Kudus, 2024)
This study aims to explore how women’s religious faith influences their interest in giving charity. The female Gen-Z has a unique and fast adaptation to digital and social media. It is important to explore their role in giving to charity. The sample size of this study is 311. Data was collected using purposive sampling based on specific criteria: female Muslim, done performing or ever performing a charity, Gen-Z between 17 to 21 years old. The research results were analyzed using Structural Equation Modeling (SEM) by employing AMOS 20; hence, Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) are essential for ensuring the reliability and validity of data analysis. EFA was analyzed through SPSS 20, while CFA and SEM were through AMOS 20. This study reveals that religious faith has a positive and significant impact on attitude and perceived behavioral control. Additionally, both attitude and perceived behavioral control significantly influence the intention of Muslim female Gen-Z to engage in charitable acts. This study is limited to female Muslim Gen-Z individuals. Therefore, future studies need to expand the demographic. This study also did not explore potential mediating or moderating factors. Therefore, future studies are encouraged to add mediating or moderating variables.